JURNALISTIK DAN HISTORIOGRAFI: ANALISIS PERAN PERS DALAM KONSTRUKSI SEJARAH INDONESIA - Hasugian, Jalatua Habungaran (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2025)
This study discusses in depth the dialectical relationship between journalism and historiography through a historical approach, while exploring how these two disciplines influence each other in the process of developing knowledge and national narratives. The phenomena studied show that journalism not only plays a role in recording actual events, but also in shaping the construction of a nation's history. Through qualitative research methods and comprehensive literature analysis, this study reveals the dynamics of interaction between journalism and historical writing in the Indonesian context. The findings in this study indicate three important points, namely: 1) the existence of epistemological similarities, where journalism and historiography have similar epistemological foundations, especially in terms of fact verification, investigative methods, and narrative presentation. Both are based on the principles of accuracy, objectivity (although not absolute), and source criticism; 2) the role of the press in the national struggle, where since the colonial era, the Indonesian press has not only been a medium of information, but also a tool for the struggle against colonialism. Newspapers at that time, such as Medan Prijaji and Sin Po had become a vessel for the articulation of nationalism as well as victims of political repression by the Dutch colonial government; and 3) the post-1998 reform dilemma, where the press freedom achieved after the 1998 reform brought new challenges, including the commercialization of the media which often contradicts journalistic idealism. The dominance of market interests often obscures the function of the press as a watchdog and contemporary historian. This study also highlights the need to recontextualize the role of the press in modern historiography. Amidst the flood of information and disinformation, journalists are required not only to meet the principle of deadlines, but also to consider the socio-historical impact of their reporting. Thus, the press must carry out its function as a recorder and interpreter of history responsibly.